1. ## Help welcome...

P = x(y+2)
Q = xy+2

Show clearly that P-Q = 2(x-1)

I am going in circles since I worked that way...

Expended x(y+2) into xy+2x

therefore

1) xy+2x-xy+2
2) 2x+2
3) Factorise... 2(x+1)

Grrr... Where am I going wrong?

HELP...

2. Originally Posted by icar36

P = x(y+2)
Q = xy+2

Show clearly that P-Q = 2(x-1)

I am going in circles since I worked that way...

Expended x(y+2) into xy+2x

therefore

1) xy+2x-(xy+2)
2) 2x+2
3) Factorise... 2(x+1)

Grrr... Where am I going wrong?

HELP...
You need the parenthesis.

$\displaystyle \underbrace{xy+2x}_{P}-(\underbrace{xy+2}_Q)$

Distribute the negative sign through the parenthesis:

$\displaystyle xy+2x-xy-2$

Simplify:

$\displaystyle xy+2x-xy-2=2x-2=\color{red}\boxed{2(x-1)}$

Do you see where you went wrong?

I hope this makes more sense now!

--Chris

3. Thank you very much Chris...

You saved my evening!

4. ## Its quite simple

xy + 2x - xy -2 = 2x-2 [You forgot to change the signs of the numbers]
2x - 2 = 2x - 2
L.H.S. = R.H.S.